A Novel STAT3 Gene Mutation Related Hyper-IgE Syndrome Misdiagnosed as Hidradenitis Suppurativa - Pragya Shrestha; Geetika Sabharwal; Gisoo Ghaffari (Case Reports in Immunology)
Although Hyper-IgE Syndrome (HIES) is a rare immunodeficiency disorder, presenting symptoms may be as common as lung and skin infections. Symptoms are usually nonspecific such as recurrent abscesses, folliculitis, and pneumonias along with skeletal abnormalities. Careful history of susceptibility to skin and lung infections, thorough family history, and findings on physical exam can guide towards the diagnosis of this often-eluded condition. Early optimization of therapy with prophylactic antibiotics can prevent recurrent infections and future complications and improve quality of life and longevity of survival. We present a case of a young female with Hyper-IgE Syndrome with a novel mutation in STAT 3 gene who initially presented with long standing history of intractable skin abscesses being managed as Hidradenitis Suppurativa.